2001
DOI: 10.1034/j.1600-0404.2001.00024.x
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disorders and depression in patients with Parkinson's disease

Abstract: The significant higher narcolepsy score in PD patients must be seen due to dopaminergic medication and PD-specific neurodegeneration and immobility rather than due to narcolepsy. This leads to the conclusion that extreme caution is advised when carrying out the SDQ and interpreting the results in various persons and patient groups with motor problems. The strong association of depression, disease severity and sleep disorders in PD patients underlines the importance of identifying and treating both conditions i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(28 citation statements)
references
References 40 publications
(50 reference statements)
4
24
0
Order By: Relevance
“…Examining the UPDRS subscales, positive correlations were found between PLMSI and both UPDRS II and UPDRS III, suggesting an increased impairment in both daily activities and motor symptoms with worsening of PLMS. An association between PLMS (assessed by questionnaire) and severity of motor symptoms was previously observed by Happe and colleagues [30]. Our study both confirms and extends these findings utilizing PSG as an objective measure for the assessment of PLMS.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Examining the UPDRS subscales, positive correlations were found between PLMSI and both UPDRS II and UPDRS III, suggesting an increased impairment in both daily activities and motor symptoms with worsening of PLMS. An association between PLMS (assessed by questionnaire) and severity of motor symptoms was previously observed by Happe and colleagues [30]. Our study both confirms and extends these findings utilizing PSG as an objective measure for the assessment of PLMS.…”
Section: Discussionsupporting
confidence: 91%
“…Some studies have found that PLMS are also more common in PD patients compared to healthy age-matched controls [3,29], whereas others did not detect significant differences [30,31]. …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicate that OSA prevalence varies from 24 to 65% [148,149,150,151]. Contradictory evidence can be found showing both a higher prevalence of OSA in PD patients than in the general population [67,149,151] and no increased risk of OSA in PD patients [152,153].…”
Section: Sleep Disordersmentioning
confidence: 88%
“…Many factors have been implicated including the use of dopaminergic therapy [2], coexisting depression [3], and more importantly the underlying disease itself [4][5][6]. Sleep disorders in PD appear to arise from a combination of neurochemical and neurodegenerative changes in central sleep regulatory centres [7][8][9].…”
Section: Introductionmentioning
confidence: 99%